Gamora's galactic showdown : starring Gamora - Snider, Brandon T. (Mighty Marvel chapter book., 2019)
Gamora sets off on a dangerous mission to recover a mysterious cube that once belonged to her father, the titan Thanos, before her sister Nebula steals it for herself.